Sword, H. (2017). Air & Light & Time & Space: How Successful Academics Write. Cambridge, MA: Harvard University Press. - Badenhorst, Cecile (Discourse and Writing/Rédactologie, 2017)
Helen Sword, author of Stylish Academic Writing (2012) and The Writer’s Diet (2016), is a staunch campaigner for shaking the dust off academic writing. She advocates that style, elegance and readability are not incompatible with rigorous research reporting. In her most recent book, Air & Light & Time & Space (2017), Sword turns her attention away from texts and shifts the spotlight onto writers. She collected extensive data to explore the habits and experiences of academic writers – how they write, when, where and how they feel when they write. Drawing on 100 interviews with successful academic writers and 1,223 questionnaires from participants at her writing workshops, Sword showcases academic writing experiences. Through extensive quotations and profiling, she illustrates the mixed, mottled and varied practices that writers engage in.